2022
DOI: 10.3390/jfb14010010
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Torque, Removal Torque, and Resonance Frequency Analysis Values of Ultrashort, Short, and Standard Dental Implants: An In Vitro Study on Polyurethane Foam Sheets

Abstract: Short implants were introduced to reduce morbidity, treatment duration, and complex bone regeneration interventions in atrophic jaws and to improve patient-reported outcomes. This study aimed to determine the insertion torque (IT), removal torque (RT), and resonance frequency analysis (RFA) values of ultrashort (3 mm length), short (7 mm length), and standard implants (10 mm length) inserted in 1-, 2-, 3-, and 4-mm thickness polyurethane sheets with densities of 10, 20, and 30 pounds per cubic foot (PCF). Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…During the removal of the BKS, the MRT showed a value of 17 N/cm during most of this unscrewing process. The MRT greater than MIT observed in this study was not reported as an occurrence in the literature for bone implants, with it being stated that the removal torque is always less than the insertion torque in both synthetic and natural bone [17,[27][28][29].…”
Section: Mit and Mrtcontrasting
confidence: 45%
“…During the removal of the BKS, the MRT showed a value of 17 N/cm during most of this unscrewing process. The MRT greater than MIT observed in this study was not reported as an occurrence in the literature for bone implants, with it being stated that the removal torque is always less than the insertion torque in both synthetic and natural bone [17,[27][28][29].…”
Section: Mit and Mrtcontrasting
confidence: 45%
“…This layering simulates the bone situation with an existing crestal cortical bone (hard bone) and an underlying cancellous bone (softer bone). The use of an additional cortical layer generally allows higher insertion torques and thus higher primary stability to be achieved than with the sole use of softer single-layer blocks [ 53 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of double-layer blocks with an additional cortical layer would probably have resulted in significantly higher insertion torque values. A study by Comuzzi et al [ 76 ] showed that the placement of standard-length implants in bilayer polyurethane foam blocks almost doubled the insertion torque compared to the monolayer block configuration (IT: 20.9 Ncm vs. 11.3 Ncm). Here, the implants were placed in monolayer polyurethane foam blocks with 10 PCF and in blocks with an additional 1 mm cortical layer (30 PCF).…”
Section: Discussionmentioning
confidence: 99%
“…Bone augmentation is also advocated but involves multiple procedures and increased postoperative discomfort, cost, and recovery time [ 22 , 42 , 43 ]. An alternative to bone grafting is short implants, defined as less than 7 mm in length [ 44 ].…”
Section: Discussionmentioning
confidence: 99%